Active Share and the Predictability of the Performance of Separate Accounts. Issue 1 (2nd January 2022) - Cremers, K. J. Martijn; Fulkerson, Jon A.; Riley, Timothy B.
Abstract: Separate accounts are a large and unique, but understudied, part of the investment management industry. Within our sample, on net, the average separate account underperforms, but for those with high active share, we find positive performance persistence. Among high active share separate accounts, a portfolio of those with strong past performance has a subsequent net alpha of 1.38% per year ( t = 2.11). That result strengthens when return dispersion is high and among separate accounts with a small cap style, a fundamental investment approach, or lower cash holdings. These results provide out-of-sample support for the predictive utility of active share.